An ab initio issues on renewable energy system integration to grid - DIPU SARKAR; Yanrenthung Odyuo (International Journal of Sustainable Energy Planning and Management, 2019)
With the introduction of new technologies such as Renewable Energy Resources (RER), Energy Storage Systems (ESS), Smart Grid technologies, Micro-Grid technologies, Distributed Generation (DG), etc., in the generation, transmission and distribution sectors, slowly but surely the entire power system scenario is changing, and it is up to the power system planners, researchers, regulators, operators and policy-makers to ensure that the power system adapts to the changes as smoothly as possible; which is easier said than done. With change comes the unknown (issues and challenges) and unless a majority of these unknowns are identified, analyzed and addressed properly, the system cannot achieve its maximum potential. The proper management, operation and integration of renewable and alternate sources of energy to existing grid is one of the promising ventures to increase the capacity of grid and at the same time make the grid more eco-friendly. This paper presents a review of the challenges and issues associated with renewable energy integration to grid and some of the existing techniques that are in use to address these issues. In order to make this review paper as detailed as possible, we have tried to identify the many issues and their corresponding solutions as much as possible.